SEARCH FOR SPATIAL VARIATIONS OF THE H2O ABUNDANCE IN THE LOWER ATMOSPHERE OF VENUS FROM NIMS-GALILEO - Drossart, P; Bezard, B; Encrenaz, T; Lellouch, E; Roos, M; Taylor, F; Collard, A; Calcutt, S; Pollack, J; Grinspoon, D; Carlson, R; Baines, K; et al. (1993)
The spectroscopic data of the Near-Infrared Mapping Spectrometer (NIMS), recorded during the Galileo flyby of Venus, are analysed to retrieve the water vapour abundance variations in the lower atmosphere of Venus at night. The 1.18 μm spectral window, which probes altitude levels below 20 km, is used for this purpose. Constraints on the CO2 continuum and far-wing opacity from existing ground-based high-resolution observations are included in the modelling of the NIMS spectra. The NIMS measurements can be fitted with a water vapour mixing ratio of 30 ± 15 ppm, in agreement with analyses of ground-based nightside observations. The water vapour abundance shows no horizontal variations exceeding 20% over a wide latitude range (40°S, 50°N) on the nightside of Venus. Within the same selection of NIMS spectra, a large enhancement in the O2 fluorescence emission at 1.27 μm is observed at a latitude of 40°S, over a spatial area about 100 km wide. © 1993.